Time-resolved collapse and revival of the Kondo state near a quantum phase transition. Issue 11 (November 2018) - Wetli, C.; Pal, S.; Kroha, J.; Kliemt, K.; Krellner, C.; Stockert, O.; v. Löhneysen, H.; Fiebig, M.
Abstract One of the most successful paradigms of many-body physics is the concept of quasiparticles: excitations in strongly interacting matter behaving like weakly interacting particles in free space. Quasiparticles in metals are very robust objects. Nevertheless, when a system's ground state undergoes a qualitative change at a quantum critical point (QCP)1, the quasiparticles may disintegrate and give way to an exotic quantum-fluid state of matter. The nature of this breakdown is intensely debated2–5, because the emergent quantum fluid dominates material properties up to high temperatures and might even be related to the occurrence of superconductivity in some compounds6 . Here we trace the dynamics of heavy-fermion quasiparticles in CeCu6−x Aux and monitor their evolution towards the QCP in time-resolved experiments, supported by many-body calculations. A terahertz pulse disrupts the many-body heavy-fermion state. Under emission of a delayed, phase-coherent terahertz reflex the heavy-fermion state recovers, with a coherence time 100 times longer than typically associated with correlated metals7, 8 . The quasiparticle weight collapses towards the QCP, yet its formation temperature remains constant—phenomena believed to be mutually exclusive. Coexistence in the same experiment calls for revisions in our view on quantum criticality. Using terahertz pulses, the quasiparticle dynamics of the heavy-fermion compound CeCu6−x Au are investigated in the vicinity of its quantum critical point.